STUDI EKSPERIMENTAL PROSES QUENCHING BERKAS PIPA PANAS SEBAGAI PEMODELAN PROSES REFLOODING TERAS REAKTOR NUKLIR - Muhadi Ayub Wasitho; Aryadi Suwono (Mesin, 1997)
To simulate the thermohydraulic characteristics of reï¬‚ooding process of a nuclear core reactor during lost of cooling accident, an experimental study using a reduced model was carried-out. The core reactor model consists of a 50 mm tubular transparent shell made of quartz and a bundle of 4 zircaloy-4 pipes of equal diameter 10.7 mm which are equipped with electrical heaters in the inside. The conï¬guration of pipe bundle is in-line with the distance between pipe axis is 14.2 mm. The pipes are identic to those usually used as nuclear reactor fuel claddings. The quenching process was done by ï¬‚ooding the pipe bundle from the bottom. The observation temperature drop of the pipes surface and temperature rise of cooling water for various wetting velocity, initial pipe temperature and cooling water were recorded and analyzed. The quenching phenomenon was also observed visually. The initial pipe temperature and wetting velocity range are 100 - 500